2015
DOI: 10.1111/jir.12190
|View full text |Cite
|
Sign up to set email alerts
|

From service quality in organisations to self‐determination at home

Abstract: Improving family members' perceptions of service quality and opening channels of communication between professionals and family members are useful strategies to facilitate parents' positive attitudes and increase the frequency of self-determination behaviours at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
2
6
0
2
Order By: Relevance
“…Second, quality was found to affect self-determination. This is consistent with the results of a study examining the relationship between service quality and self-determination using data on daycare center users, which showed that service quality affects self-determination behaviour [46]. It is also consistent with a study that examined the relationship between service quality and satisfaction mediated by self-determination in a model of mobile banking users, and found that service quality influences self-determination [17].…”
Section: Discussionsupporting
confidence: 89%
“…Second, quality was found to affect self-determination. This is consistent with the results of a study examining the relationship between service quality and self-determination using data on daycare center users, which showed that service quality affects self-determination behaviour [46]. It is also consistent with a study that examined the relationship between service quality and satisfaction mediated by self-determination in a model of mobile banking users, and found that service quality influences self-determination [17].…”
Section: Discussionsupporting
confidence: 89%
“…In promoting positive attitudes toward self-determination in families and encouraging self-determination behaviors at home, organizations for PIDD would play a significant role. Martínez-Tur et al [5] confirmed this idea in their study. They observed that communication openness about self-determination (family members perceive that they can discuss self-determination with the staff) improves the attitudes of family members and increases the self-determination behaviors of PIDD at home.…”
Section: Opinionsupporting
confidence: 62%
“…Otra línea de trabajo en discapacidad intelectual se refiere a las intervenciones con los padres y cuidadores. La literatura describe experiencias positivas para el desarrollo de actitudes facilitadoras de autonomía en sus hijos/as, así como de beneficios para su propio bienestar emocional, tanto con intervenciones a cargo de profesionales como de actividades de apoyo mutuo entre padres (Heller y Schindler, 2009;Carter et al, 2013;Martínez-Tur, Moliner, Peñarroja, Gracia y Peiró, 2015;Leonard et al, 2016).…”
Section: Resultados De La Revisión De Literaturaunclassified
“…La sobreprotección de padres y cuidadores contribuye a limitar la autonomía e independencia de las personas con DI (Power, 2008;Björnsdóttir et al, 2015). Experiencias positivas con programas de apoyo a padres en el desarrollo de actitudes facilitadoras de autonomía (Leonard et al, 2016;Carter et al, 2013;Heller y Schindler, 2009;Martínez-Tur et al, 2015). Las familias y los cuidadores pueden ser tanto barreras como facilitadores del ejercicio de derechos humanos (Kripke, 2016;Hillman et al, 2012).…”
Section: Inclusión Social: Participación Comunitariaunclassified